Entre o nacionalismo político e o nacionalismo econômico: representações do Brasil na Revista Veja (1968-1974) - Carvalho, Tamiris (2014)
This work is inserted on Line Integration, Politics and Frontier Research Program Graduate in History of the Federal University of Santa Maria (UFSM). That aimed to understand the role of Veja magazine, in the period of civil - military dictatorship in Brazil (1968/1974) in constructing representations of the national enemy. Through editorials which seek to realize the image of Brazil built this historical moment and how it relates to those considered non-being of Brazil, especially the communists at this historic moment. We also analyze the metamorphosis of the discourse of Veja Magazine since 1970. First seek to understand the context in which our subject is inserted following chapters presents the analysis of the sources. The sources used in the dissertation are available online at the journal's site View. You can access all copies since the first in 1968 until today. We will use as a source of research reports and the editorials concerning Brazil.